1998
DOI: 10.1111/j.1945-5100.1998.tb01682.x
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of nanophase magnetite in Martian meteorite Allan Hills 84001: Implications for biogenic mineralization

Abstract: Abstract-Crystallographic relationships between magnetite, sulfides, and carbonate rosettes in fracture zones of the Allan Hills (ALH) 84001 Martian meteorite have been studied using analytical electron microscopy. We have focused on those magnetite grains whose growth mechanisms can be rigorously established from their crystallographic properties. Individual magnetite nanocrystals on the surfaces of carbonates are epitaxially intergrown with one another in "stacks" of single-domain crystals. Other magnetite n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 34 publications
(43 reference statements)
2
43
0
Order By: Relevance
“…The current balance of evidence does not strongly support the biogenic theory of origin for ALH84001 carbonates (Scott, 1999;Steele et al, 2000;Kathie et al, 2000;Bradley et al, 1998;. The best argument for a biological origin rests with the morphology of some of the magnetite grains.…”
Section: Suggested Relic Biological Activity In Alh84001mentioning
confidence: 83%
See 1 more Smart Citation
“…The current balance of evidence does not strongly support the biogenic theory of origin for ALH84001 carbonates (Scott, 1999;Steele et al, 2000;Kathie et al, 2000;Bradley et al, 1998;. The best argument for a biological origin rests with the morphology of some of the magnetite grains.…”
Section: Suggested Relic Biological Activity In Alh84001mentioning
confidence: 83%
“…Brearley suggested that the phlogopite was derived through the breakdown of pre-existing clay during shock heating at <500 • C. Treiman (1998a) documented fracturing episodes within ALH84001 and proposed that the carbonate had experienced 4 discrete deformation events. Bradley et al (1998) also carefully documented the magnetite structures around the carbonate rosettes and suggested that whisker-shaped grains they found were most consistent with precipitation at high temperatures (500 − 800 • C) from a vapour. This was taken by Scott (1999) to be a result of the shock remobilisation of pre-existing carbonates and resultant break down of Fe-carbonate to a magnetite-bearing assemblage.…”
Section: High Temperature: Shock Remobilisation Andmentioning
confidence: 99%
“…Bradley et al (1998) also carefully documented the magnetite structures around the carbonate rosettes and suggested that whisker-shaped grains they found were most consistent with precipitation at high temperatures (500 − 800…”
Section: High Temperature: Shock Remobilisation Andmentioning
confidence: 99%
“…Although magnetite forms predominantly diamond-shape octahedrons {111} in the cubic crystal classes, it also crystallizes in several other forms (e.g., dodecahedral and cubic). Unusual, elongated forms known as whiskers have also been reported to form from a vapor phase at high temperatures (3). Magnetite crystals formed by magnetotactic bacteria (magnetosomes) also have a variety of distinct morphologies.…”
mentioning
confidence: 99%